HABITAT SUITABILITY INDEX (HSI) MODEL OF PUNJAB URIAL (OVIS VEGNEI PUNJABIENSIS) IN PAKISTAN - S. Suleman; W. A. Khan; K. M. Anjum; W. Shehzad; S. G. M. Hashmi (Journal of Animal and Plant Sciences, 2020)
Unprecedented losses in biodiversity due to habitat loss and fragmentations in the current era have not only alarmed the scientists worldwide but also urged the need to devise suitable conservation strategies which are impossible without understanding the habitat requirements of the concerned species. Among many conservational methods Habitat suitability models are effective for identification of potential habitat and its relationship with the species. Punjab Urial is an endangered mammalian species of Kala Chitta Range and Salt Range in the Punjab, Pakistan. Maxent model was applied to identify the potential habitat by applying 120 sighting point, topographical and current bioclimatic variables. Possible area under receiver operating characteristics curves (AUC) test for current prediction is 0.988 that shows significant correlation between testing points and variables. In Pakistan total 3477 km2 area is suitable for Punjab Urial and potential habitats lie in limited areas in Rawalpindi, Sargodha, Gujrat, Mardan, Swabi, Nowshera, North Wziristan, Bannu, Dera Ismail Khan, Laki-Marwat and some area in Azad Jammu & Kashmir. Habitat of Punjab Urial is shrinking due to certain reasons including habitat fragmentation. In-situ and Ex-situ techniques are the major recommendation for species conservation in suitable and potential habitat of Punjab Urial.
Keywords: HSI model; Kala Chitta Range; Maxent; Punjab Urial; Salt Range